2021
DOI: 10.1016/j.yjmcc.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure impairs the mechanotransduction properties of human cardiac pericytes

Abstract: The prominent impact that coronary microcirculation disease (CMD) exerts on heart failure symptoms and prognosis, even in the presence of macrovascular atherosclerosis, has been recently acknowledged. Experimental delivery of pericytes in non-revascularized myocardial infarction improves cardiac function by stimulating angiogenesis and myocardial perfusion.Aim of this work is to verify if pericytes (Pc) residing in ischemic failing human hearts display altered mechano-transduction properties and to assess whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Unfortunately, the field of myocardial biology has neglected the pericyte, a cell type of high potential significance in cardiac homeostasis and disease. Associative evidence suggests that pericytes may be involved in early myocardial ischemic injury, 26 may respond to myocardial mechanical stress 25 and neurohumoral stimulation, 9 and may be implicated in fibrosis of the remodeling heart. 65 , 66 Moreover, some studies have suggested that subpopulations of pericytes may have reparative, angiogenic, and even regenerative potential in models of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the field of myocardial biology has neglected the pericyte, a cell type of high potential significance in cardiac homeostasis and disease. Associative evidence suggests that pericytes may be involved in early myocardial ischemic injury, 26 may respond to myocardial mechanical stress 25 and neurohumoral stimulation, 9 and may be implicated in fibrosis of the remodeling heart. 65 , 66 Moreover, some studies have suggested that subpopulations of pericytes may have reparative, angiogenic, and even regenerative potential in models of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cells harvested from patients with heart failure have demonstrated that pericytes from cardiomyopathic hearts exhibit impaired mechanotransduction. 25 Moreover, animal model studies have suggested that pericytes may play a role in early postischemic microvascular injury, 26 may be involved in “no‐reflow” following ischemia and reperfusion, 27 , 28 and may contribute to the pathogenesis of the cardiomyopathy associated with receptor tyrosine kinase inhibitor treatment. 29 However, investigations documenting the involvement of pericytes in myocardial diseases using genetic approaches are lacking.…”
mentioning
confidence: 99%
“…Furthermore, fibronectin induces higher rates of pericyte proliferation and migration (Tigges et al, 2013), an observation that may explain the increased fibronectin levels observed during angiogenesis and development, where pericyte activation and migration are crucial. Interestingly, the mechanoresponse to substrate composition and stiffness is defective in pericytes isolated from end-stage ischemic hearts (Rolle et al, 2020), illustrating the crucial yet poorly understood role of pericyte mechanobiology in diseases.…”
Section: Investigating Bm Interactionsmentioning
confidence: 99%
“…To test our method in a clinically relevant model, we collected samples of cardiac pericytes (CPcs) obtained from patients undergoing cardiac transplantation (E-CPcs) or from healthy donors (D-CPcs). Previous investigation in this model provided preliminary evidence that E-CPcs residing in ischemic failing human hearts are enriched by senescent cells [ 22 , 23 ]. E-CPcs were characterized by reduced proliferation rate (significantly reduced % of Ki-67 positive cells) and increased % of phosphorylated histone H2AX (γH2AX), as well as by increased SA-β-gal-positive cells (measured by microscopy) and activity (measured by Spider-βGAL flow cytometry assay), reminiscent of senescence ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we also applied this method to “ex-vivo” samples of CPc from donors and explanted hearts. It has been previously shown that E-CPc residing in ischemic failing human hearts are senescent and display altered mechano-transduction properties [ 22 , 23 ]. Following a few days in culture, we observed that these cells are similar to senescent cells with the typical morphological changes and an increase in many markers associated with cellular senescence.…”
Section: Discussionmentioning
confidence: 99%